2017
DOI: 10.1152/ajpheart.00101.2017
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter 4-deficient hearts develop maladaptive hypertrophy in response to physiological or pathological stresses

Abstract: Pathological cardiac hypertrophy may be associated with reduced expression of glucose transporter 4 (GLUT4) in contrast to exercise-induced cardiac hypertrophy, where GLUT4 levels are increased. However, mice with cardiac-specific deletion of GLUT4 (G4H) have normal cardiac function in the unstressed state. This study tested the hypothesis that cardiac GLUT4 is required for myocardial adaptations to hemodynamic demands. G4H and control littermates were subjected to either a pathological model of left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…In this context, one possible mechanism is the compromised GLUT4 translocation. Previous studies showed that GLUT4 is an important mediator of enhanced glycolysis and maintaining ATP concentration under various pathological conditions, including IRI [2,8,9,12]. However, significant decreases in the sarcolemmal GLUT4 expression were observed in insulinresistant obese mouse hearts [13,14], consistent with the present findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this context, one possible mechanism is the compromised GLUT4 translocation. Previous studies showed that GLUT4 is an important mediator of enhanced glycolysis and maintaining ATP concentration under various pathological conditions, including IRI [2,8,9,12]. However, significant decreases in the sarcolemmal GLUT4 expression were observed in insulinresistant obese mouse hearts [13,14], consistent with the present findings.…”
Section: Discussionsupporting
confidence: 92%
“…GLUT4 resides mainly in the intracellular vesicles under basal conditions and is translocated to the plasma membrane in response to insulin as well as other pathological processes, such as ischemic insult. It was previously reported that GLUT4-mediated enhanced glucose transport represents an essential protective mechanism against IRI and other pathological stresses [2,8,9,11,12]. However, it was also reported that the cardiac GLUT4 expression is decreased under insulin-resistant conditions, such as diabetes, in association with the reduction in glucose uptake, leading to impaired glucose utilization in the heart [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ceramide (a well-studied sphingolipid) has been linked with cardiac disease and/or pathology in humans and rodents (Chokshi et al, 2012;Havulinna et al, 2016;Ji et al, 2017;Sapra et al, 2014;Yu et al, 2015). In contrast, reduced cardiac ceramide was reported in exercise-trained rodents (Baranowski et al, 2008;Liu et al, 2009;Wende et al, 2017). In the current study, ceramides (as a class) were not decreased in the hearts of swimming mice but tended to be lower ( Figure 3C).…”
Section: Cardiac Lipidomementioning
confidence: 99%
“…On the other hand, mice with cardiac-specific GLUT4 deletion developed significantly greater hypertrophy and more severe contractile dysfunction after TAC compared to their wild-type littermates. 95 This latter study suggests that GLUT4 may be required (and therefore more important than GLUT1) for maintenance of cardiac structure and function in response to PO.…”
Section: Glucose Transportersmentioning
confidence: 92%